The Relationship of Insulin Resistance and Systemic Inflammation with Cardiovascular Outcomes in Non-Diabetic Patients Undergoing Coronary Artery Bypass Grafting - Xie Y; Chen H; Gao Y; He H; Wang Z; Zhang Y; Zhou Q; Liu L; Zheng J (Journal of Inflammation Research)
Yingying Xie,1– 3,* Hao Chen,2,4,* Yanxiang Gao,3 Haoming He,3 Zhe Wang,3 Yaru Zhang,3 Qiaochu Zhou,3 Ling Liu,2 Jingang Zheng1,3 1Department of Cardiology, China-Japan Friendship Hospital (Institute of Clinical Medical Sciences), Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Cardiology, The Second Xiangya Hospital of Central South University, Changsha, People’s Republic of China; 3Department of Cardiology, China-Japan Friendship Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 4Department of Cardiology, The Second Affiliated Hospital of South China University, Hengyang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jingang Zheng, Department of Cardiology, China-Japan Friendship Hospital, Chinese Academy of Medical Sciences & Peking Union Medical College, No. 2 East Yinghua Road, Chaoyang District, Beijing, 100029, People’s Republic of China, Fax +86-010-84205026, Email mdjingangzheng@yeah.net Ling Liu, Department of Cardiovascular Medicine, The Second Xiangya Hospital, Central South University, No. 139 Renmin Road, Changsha, Hunan, 410011, People’s Republic of China, Fax +860731-85295407, Email feliuling@csu.edu.cnBackground: Insulin resistance (IR) is linked to adverse cardiovascular outcomes, but its mechanisms are not fully understood. This study investigates the relationship between IR and systemic inflammation and evaluates how systemic inflammation affects the correlation between IR and prognosis in non-diabetic patients undergoing coronary artery bypass grafting (CABG).Methods: This study enrolled 1,658 patients post-CABG. IR was assessed via the estimated glucose disposal rate (eGDR), and systemic inflammation was measured by C-reactive protein (CRP) levels. The correlation between eGDR and CRP was analyzed using linear regression. Associations of eGDR and CRP with major adverse cardiovascular and cerebrovascular events (MACCEs) were evaluated through the Kaplan–Meier method, restricted cubic splines (RCS), and adjusted Cox regression analyses. A novel two-stage regression method for survival data was used in the mediation analysis.Results: Over a median follow-up period of 60.9 months, 414 MACCEs cases were documented. The RCS analysis revealed an L-shaped association between eGDR and MACCEs with an approximate threshold of 8 mg/kg/min, whereas CRP exhibited a linear positive dose-response relationship with MACCEs. Compared with individuals in the high eGDR and low CRP group (eGDR > 8 and CRP < 3), those in the low eGDR and high CRP group (eGDR ≤ 8 and CRP ≥ 3) showed the highest risk for MACCEs (hazard ratio [HR] = 2.282, 95% confidence interval [CI] 1.749– 2.978). Mediation analysis indicated that CRP levels mediated 12.3% of the correlation between eGDR and MACCEs.Conclusion: eGDR showed a negative correlation with CRP levels, and their synergistic relationship enhanced the prediction of MACCEs in non-diabetic patients undergoing CABG. Additionally, CRP levels partially mediated the association between eGDR and MACCEs. Anti-inflammatory treatment for non-diabetic individuals with high IR who underwent CABG may offer further benefits.Keywords: insulin resistance, systemic inflammation, non-diabetic, coronary artery bypass grafting